A postulated model for photoimmunopathogenesis of chronic actinic dermatitis around adaptive immunity, including Th17 cells, Tregs, TRMs, cytotoxic T cells, and/or common‐γ chain receptor+ cells. Issue 2 (22nd December 2022) - Kim, Jung‐Hwan; Kim, Ho‐Jin; Yoo, Dong‐Wha; Park, Kyung‐Deok; Kwon, Hyeok‐Jin; Seo, Jung‐Wan; Kim, Tae‐Hoon; Yoon, Jung‐Ho; Seong, Seol‐Hwa; Jang, Min‐Soo; Kim, Ki‐Ho
Abstract: Background/Purpose: The pathogenesis of chronic actinic dermatitis (CAD) is more complicated than other photodermatoses. However, the relationship between the clinical severity of CAD and the offending photocontact or contact allergens or both, and the correlations of CAD immunopathogenesis with the immunoregulatory molecules involved in adaptive immunity are yet to be investigated. Methods: We performed phototesting with broad‐spectrum ultraviolet (UV) B, UVA, and visible light to establish the presence of photosensitivity in 121 patients with CAD, together with photopatch and contact patch testing. Nine patients with CAD were selected according to their clinical severity score for CAD (CSS‐CAD), and triple direct immunofluorescence analysis was performed with paraffin‐embedded skin biopsy samples. Results: As CSS‐CAD was closely correlated with the multiplicity of photo(contact) allergens, particularly photoallergens, three or more photoallergens were detected in the severe CAD group (52.5%); less in the moderate group (32.8%); and only one in the mild group (14.8%; P = .025). In the groups showing greater severity of disease, the absolute numbers of IFN‐γ +, IL‐17 +, CD4+, CD8+, common‐γ chain receptor (common‐γCR) +, and CD69 + tissue‐resident memory cells increased on average; there was also an increase in the CD4+/CD8+ cell ratio, with the more severely affected groups. However, the levels of TNF‐α + and FoxP3 + regulatory T (Treg) cells and the mean IL‐17/IFN‐γ cell ratio decreased in the more severely affected CSS‐CAD subgroups. Conclusions: Based on the clinical analysis and immunopathogenic results, avoidance of excessive sun exposure, and topical and systemic blocking agents for photo(contact) allergens are recommended. Additionally, conventional immunomodulators and emerging agents including JAK–STAT inhibitors may be administered for CAD treatment in the future.